ETIKA SUKSESI DI ORGANISASI DAKWAH - Wahyudiyanto, Dhanny (STID Al-Hadid, 2021)
Da’wah organization elites often play organizational politics in their organization. It sometimes leads to resistance among cadres or members, negative image from public, and even cleavage in their da’wah organization. On the other hand, politics is a natural impulse, including in succession process of organizational leadership. Organizational politics has positivity when handled in good goals and ways. Therefore, this paper is written to formulate political ethics in da’wah organization in the context of leadership succession. It uses a conceptual qualitative method by adapting concepts of Islamic political ethics and organizational politics in the context of leadership succession of da’wah organization. It indicates Islamic political ethics in leadership succession broadly include aspects of goals and ways. Political goals in leadership succession must be aligned with da’wah organization’s goals and lead to basic orientation of organizational leadership succession. Ways to gain power based on Islamic political ethics in the context of leadership succession should be conducted through self-quality improvements including aspects of idealism, morals, and abilities. In the succession process involving competition system, each actor must uphold sportsmanship, show self-qualities objectively to voters. If it is contesting the candidates, each actor must maintain delivery of political products to not emerge destructive conflicts.